2016
DOI: 10.1080/14992027.2016.1257164
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic reflexes are common but not pervasive: evidence from the National Health and Nutrition Examination Survey, 1999–2012

Abstract: Acoustic reflexes are not sufficiently prevalent to be included in DRC and HHA for impulsive noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…The AN must be intact to initiate the acoustic reflex; the strength of the acoustic reflex is reduced in mice with synaptopathy (Valero et al 2016;Valero et al 2018) and this may prove to be a useful metric in humans as well. MEMRs are known to be weak, or absent, in a subset of the population (Flamme et al 2017;McGregor et al 2018), and it has been suggested that synaptopathic injury could underlie this observed individual variability (Wojtczak et al 2017). Use of a wideband probe and a broadband activator stimulus has been shown to lower MEMR thresholds compared to the standard 226 Hz probe tone used clinically, which could perhaps improve the ability to reliably detect MEMR responses in future studies (Feeney et al 2017).…”
Section: Suggestions For Methodological Approaches To Investigate Synmentioning
confidence: 99%
“…The AN must be intact to initiate the acoustic reflex; the strength of the acoustic reflex is reduced in mice with synaptopathy (Valero et al 2016;Valero et al 2018) and this may prove to be a useful metric in humans as well. MEMRs are known to be weak, or absent, in a subset of the population (Flamme et al 2017;McGregor et al 2018), and it has been suggested that synaptopathic injury could underlie this observed individual variability (Wojtczak et al 2017). Use of a wideband probe and a broadband activator stimulus has been shown to lower MEMR thresholds compared to the standard 226 Hz probe tone used clinically, which could perhaps improve the ability to reliably detect MEMR responses in future studies (Feeney et al 2017).…”
Section: Suggestions For Methodological Approaches To Investigate Synmentioning
confidence: 99%
“…With respect to the differential diagnosis of cochlear synaptopathy, the amplitude of the middle ear muscle reflex has been successfully associated with cochlear synaptopathy in mouse models (Valero, Hancock and Liberman 2016;Valero et al 2018). Middle ear muscle reflexes are weak, or absent, in a subset of the population (Flamme et al 2017;McGregor et al 2018), leading several investigators to suggest that noise exposure resulting in cochlear synaptopathic injury could provide one explanation for individual variability in human participants (Wojtczak, Beim, and Oxenham 2017;McGregor et al 2018). There is also the thought that the amount of energy reaching the cochlea is a function of the wide band reflectance or admittance.…”
Section: Middle Ear Reflex Testsmentioning
confidence: 99%
“…This limit is equivalent to the lower boundary of the 90 % confidence interval for a prevalence proportion that is 0.95 or more. The AR was not determined to be pervasive in a prior study (Flamme et al, 2017), and the current study was conducted to confirm or disconfirm these results with a different study population and measurement instrument.…”
Section: Introductionmentioning
confidence: 64%
“…Factors such as age (Hodges & Ruth, 1987; Hall, 1982), attention (Durrant & Shallop, 1969; Robinette & Snyder, 1982), middle ear abnormalities (Jerger et al, 1974a; Nozza et al, 1992), hearing status (Gelfand, Piper & Silman, 1983), and gender (Flamme et al, 2017; Hall, 1982) have been shown to influence the likelihood of observing an AR. For example, an AR is more likely to be observed in females as compared to males (Flamme et al, 2017), young adults as compared to older adults (Flamme et al, 2017; Silman, 1979), and in individuals with normal hearing as compared to individuals with hearing impairments (Silman, Popelka & Gelfand, 1978; Jerger, Jerger & Mauldin, 1972).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation